2018
DOI: 10.1074/jbc.ra118.002357
|View full text |Cite
|
Sign up to set email alerts
|

Genetic code expansion and live cell imaging reveal that Thr-308 phosphorylation is irreplaceable and sufficient for Akt1 activity

Abstract: The proto-oncogene Akt/protein kinase B (PKB) is a pivotal signal transducer for growth and survival. Growth factor stimulation leads to Akt phosphorylation at two regulatory sites (Thr-308 and Ser-473), acutely activating Akt signaling. Delineating the exact role of each regulatory site is, however, technically challenging and has remained elusive. Here, we used genetic code expansion to produce site-specifically phosphorylated Akt1 to dissect the contribution of each regulatory site to Akt1 activity. We achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
133
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(149 citation statements)
references
References 67 publications
(73 reference statements)
13
133
3
Order By: Relevance
“…We also observed in COS-7 cells that pSer473 is dispensable for Akt1 signaling and phosphorylation of Thr308 alone was sufficient for maximal Akt1 signal prorogation. These results indicated Thr308 phosphorylation status is a superior biomarker for Akt1 activity [11] and called into question the frequent use of Ser473 phosphorylation as a diagnostic marker for Akt1 activity in cancer patients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also observed in COS-7 cells that pSer473 is dispensable for Akt1 signaling and phosphorylation of Thr308 alone was sufficient for maximal Akt1 signal prorogation. These results indicated Thr308 phosphorylation status is a superior biomarker for Akt1 activity [11] and called into question the frequent use of Ser473 phosphorylation as a diagnostic marker for Akt1 activity in cancer patients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging our ability to produce Akt1 protein in specifically phosphorylated forms (Figure 2), we recently quantified the precise contribution of pThr308 and pSer473 to Akt1 activity in vitro and in mammalian cells [11]. In studies with purified full length Akt1, we found that pAkt1 T308 achieves 30% of the activity of the doubly phosphorylated kinase.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations